2017
DOI: 10.3892/ol.2017.5563
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing cimetidine for cholangiocarcinoma: Antitumor effects in vitro and in vivo

Abstract: Abstract. Cimetidine is a histamine type-2 (H 2 ) receptor antagonist that has been demonstrated to have antitumor effects on various types of malignancy. However, its effect on cholangiocarcinoma (CCA), a chemotherapy-resistant bile duct tumor, has yet to be investigated. In the present study, the antitumor activity of cimetidine in vitro and in vivo was evaluated. A methylthiotetrazole assay revealed that the proliferation of certain CCA cell lines was inhibited by cimetidine, which induced the caspase-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results indicated that non-antineoplastic agents interacted with certain genes implicated in CCA. Cimetidine, a histamine type 2 antagonist, is used to treat heartburn and peptic ulcer; however, data also indicates that cimetidine may contribute to growth inhibition and apoptosis induction in CCA in vitro and in vivo ( 57 ). Valproic acid is used to treat bipolar disorders and prevent migraine headaches; previous study identified that it may inhibit the growth of CCA cell lines (TFK-1, QBC939 and CCLP1) by inducing cell cycle arrest and promoting cell differentiation via induction of dendrite-like structures ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that non-antineoplastic agents interacted with certain genes implicated in CCA. Cimetidine, a histamine type 2 antagonist, is used to treat heartburn and peptic ulcer; however, data also indicates that cimetidine may contribute to growth inhibition and apoptosis induction in CCA in vitro and in vivo ( 57 ). Valproic acid is used to treat bipolar disorders and prevent migraine headaches; previous study identified that it may inhibit the growth of CCA cell lines (TFK-1, QBC939 and CCLP1) by inducing cell cycle arrest and promoting cell differentiation via induction of dendrite-like structures ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated the potential of propofol, an intravenous anesthetic drug, to be repurposed to overcome resistance to imatinib in chronic myeloid leukemia treatment ( 123 ). Cimetidine, a drug used in the treatment of peptic ulcers, induces the apoptotic death of cholangiocarcinoma cells by the suppression of Akt phosphorylation and may be an effective candidate for future treatments ( 124 ). A well-known antifungal agent, itraconazole, has demonstrated anticancer activity in various cell lines by inhibiting Akt/mTOR signaling ( 125 ).…”
Section: Repurposing Studiesmentioning
confidence: 99%
“…In this sense, novel clinical applications for histamine H 1 receptor antagonists/inverse agonists are currently being studied for the management of different pathological situations, such as inflammatory-related conditions (in combination with glucocorticoids) (Zappia et al, 2015), analgesia (Stein et al, 2016) or neurodegenerative and sleep disorders (Kim and Song, 2017;Krystal, 2015). In the same way, evidence for anti-cancer effects of the histamine H 2 receptor inverse agonist cimetidine has been reported in various types of neoplasias, including glioblastoma, cholangiocarcinoma, malignant melanoma, renal cell carcinoma, colorectal and gastric cancer (Dana et al, 2017;Pantziarka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%